Acclimatization of virus-free tissue culture plants of cassava through semi autotropic hydroponics technique - Iype Praveen Thomas; U. Adarsh Krishnan; J. Sreekumar; T. Makeshkumar (JOURNAL OF ROOT CROPS, 2025)
Abstract Manihot esculenta Crantz, commonly known as cassava, belongs to the Euphorbiaceae family, and is a crucial tuber crop that serves as a staple food for millions of people worldwide. The acclimatization of cassava tissue culture plantlets faces challenges due to temperature, humidity and microfauna which leads to high mortality rate. To overcome these limitations, semi-autotrophic hydroponics (SAH) emerges as a promising technique for enhancing the large-scale production of cassava plants free from CMD and refining the process of acclimating in vitro plants to external conditions. This study aimed to evaluate the performance of cassava tissue culture plantlets using different substrates for rapid multiplication. Transplantation of in vitro nodal segments into three distinct growing substrates: cocopeat (CP), sawdust (SD), and sand (S) were tried in the experiment. These substrates were moistened with either Murashige and Skoog liquid solution or an experimental SAH solution for 60 days. The results showed that survival was significantly influenced by the substrate used, with cocopeat demonstrating the highest rate of more than 90%. The survival rate, shoot length, root numbers, and leaf numbers were collected at the end of one week. The differences in survival rates and growth parameters were significant among substrates (p<0.001). Keywords: Cassava, Cocopeat, Saw Dust, Sand, Semi-Autotrophic Hydroponics (SAH)